Two sub-millimetre bright protoclusters bounding the epoch of peak star-formation activity. Issue 2 (26th June 2019) - Lacaille, Kevin M; Chapman, Scott C; Smail, Ian; Steidel, C C; Blain, A W; Geach, J; Golob, A; Gurwell, M; Ivison, R J; Reddy, N; Sawicki, M
ABSTRACT: We present James Clerk Maxwell Telescope Submillimetre Common-User Bolometer Array 2 (SCUBA-2) 850 and 450$μ$ m observations (σ850 ∼ 0.5 mJy, σ450 ∼ 5 mJy) of the HS1549+19 and HS1700+64 survey fields containing two of the largest known galaxy overdensities at z = 2.85 and 2.30, respectively. We detect 56 sub-millimetre galaxies (SMGs) with SNR > 4 over ∼50 arcmin 2 at 850$μ$ m with flux densities of 3–17 mJy. The number counts indicate overdensities in the 3-arcmin diameter core region (∼1.5 Mpc at z = 2.5) of$6^{+4}_{-2}×$ (HS1549) and$4^{+6}_{-2}×$ (HS1700) compared to blank field surveys. Within these core regions, we spectroscopically confirm that approximately one-third of the SMGs lie at the protocluster redshifts for both HS1549 and HS1700. We use statistical identifications of other SMGs in the wider fields to constrain an additional four candidate protocluster members in each system. We combine multiwavelength estimates of the star-formation rates (SFRs) from Lyman-break dropout- and narrow-band-selected galaxies, and the SCUBA-2 SMGs, to estimate total SFRs of 12 500 ± 2800 M⊙ yr −1 (4900 ± 1200 M⊙ yr −1 ) in HS1549 (HS1700), and SFR densities (SFRDs) within the central 1.5-Mpc diameter of each protocluster to be 3000 ± 900 M⊙ yr −1 Mpc −3 (1300 ± 400 M⊙ yr −1 Mpc −3 ) in the HS1549 (HS1700) protocluster, ∼10 4 × larger than the global SFRDs found at their respective epochs, due to the concentration of star-forming galaxies in the small volume of the dense cluster cores. Our results suggest centrally concentrated starbursts within protoclusters may be a relatively common scenario for the build-up of mass in rich clusters assembling at z ≳ 2.